AN EXPERIMENTAL STUDY OF BURR FORMATION IN DRILLING AND SLOT-END MILLING OPERATIONS (Journal of Engineering, 2009)
This paper presents the results of an experimental study on the influence of the main cutting parameters on burr formation and its types in drilling and slot-end milling operations to machine low carbon and stain -less steels using HSS cutting tools and cutting fluid. Particular attention was focused on the relation between the burr type and size and cutting parameters. Therefore, a wide range of cutting speeds, feed rates, and dept of cuts were investigated to explore the optimum cutting conditions. Burr heights were measured and anal- lyzed at different machining conditions to determine the effect of the cutting speed, feed rate, and depth of cut on burr formation. The data obtained for low carbon steel were compared with those for stainless steel. Different diameters of HSS twist drills were used to observe their effects on drilling burr formation. The quantitative measurements of burrs height yield much useful information because relatively uniform small and large burrs were formed under these conditions